Molecular genetics of beta thalassaemia in Asian Indians - Varawalla, N; Varawalla, Nermeen Y (1992)
The primary aim of this thesis was to outline an approach for the prenatal diagnosis of β-thalassaemia in the Asian Indian population by DNA analysis. A polymerase chain reaction (PCR) based, nonradioactive and rapid technique, allele specific PCR, was successfully developed for the detection of β-thalassaemia mutations. A large sample of 656 unrelated carriers from seven different regions of the Indian subcontinent was studied by allele specific PCR and DNA sequence analysis. Sixteen different β-thalassaemia mutations were identified, two of which were new mutations. Of these five common mutations accounted for 91.7% of β-thalassaemia alleles. The β-globin gene haplotypes of 419 β-Th and 196 β - A chromosomes were constructed. On analysis of which it was inferred that β-thalassaemia mutations occurred relatively recently on existing chromosomal backgrounds and then they experienced positive selection. A strong but not invariant haplotype-mutation linkage was observed. A regional variation in the distribution of β-thalassaemia mutations was found. α-Globin gene mapping studies identifed the single α-globin gene deletion in 24 out of 51 unrelated Asian Indians who were suspected to have α-thalassaemia. It is likely that the remaining carriers have nondeletional α-thalassaemia determinants. To perform preimplantation diagnosis of β-thalassaemia, by analysis of a 10-30 cell embryonic biopsy, a PCR protocol was developed. Using two rounds of PCR with nested primers, successful amplification of a 597 bp fragment of the β-globin gene was achieved from as few as two embryonic cells. The problem of false positive amplification was encountered which appeared to be resolved by UV transillumination of the pre-amplification PCR mix. By allele specific PCR with nested primers it was possible to identify the presence or absence of five β-thalassaemia mutations from 10 pg of template DNA (equivalent to approximately two diploid cells). Thalassaemia control in India is a complex issue; the financial, social and demographic factors involved were considered and recommendations made.